Sosialisasi Moderasi Beragama di Kelurahan Pasar Doloksanggul Kabupaten Humbang Hasundutan (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Abstract: The promotion of religious moderation in society can prevent potential conflicts and build bridges of brotherhood between religious communities. Likewise, the IAKN Tarutung Postgraduate Christian religious education masters study program through Community Service activities in Doloksanggul sub-district, Humbang Hasundutan Regency. Community service activities participants consist of lecturers and students. Through this activity, the Christian religious education Masters Study Program also carried out research aimed at finding out the benefits of socializing religious moderation in Doloksanggul Village, Humbang Hasundutan Regency. The material content of religious socialization activities contains 4 indicators as follows: 1. Teaching the ability to live with differences, 2. Building mutual trust, 3. Mutual understanding, 4. Being respectful of each other. This method of implementing community service applies the Participatory Action Research (PAR) method. Community service activities will be carried out from May to August 2024 with a target group of 33 adult people. The community is taught to understand the 4 indicators above through the guidance of the Community service activities team. The benefits of socializing religious moderation in Doloksanggul Village, Humbang Hasundutan Regency can be seen from the number of respondents who answered the question yes on average, 31.6 with a percentage of 95.85%, while the number of respondents who answered no was 1.4 with a percentage of 4.15%. This means that the material content of religious moderation socialization activities in Doloksanggul Village, Humbang Hasundutan Regency is very useful in preventing potential conflicts and building bridges of brotherhood between religious communities.